Penguatan Kelembagaan Credit Union Melalui Perencanaan Keuangan - Cicilia Erna Susilawati; Nekhasius Agus Sunarjanto; Herlina Yoka Roida; Cyrillius Martono; Erick Teofilus Gunawan (LPPM, Universitas Katolik Widya Mandala Surabaya, 2021)
Financial planning is an important part in improving Credit Union (CU) institutions, especially for management. CU as an institution engaged in community empowerment must understand and develop its management with good financial planning. So that it can carry out the empowerment of members properly and correctly. The implementation of ABDIMAS has a positive impact on the management. Hopefully the impact of this training does not stop at the management but extends to members and the wider community